A comparative study of prescribing and transcribing between the women hospital pharmacy and the ASHP: a benchmark approach. (4th January 2010) - Salaheldin, Salaheldin Ismail; Mukhalalati, Banan A.
The aim of this case study is to compare the performance of the Pharmacy Department in the Women Hospital of the Hamad Hospital Corporation (HMC) of Qatar, with that of the American Society of Health System Pharmacists (ASHP) national survey in terms of prescribing and transcribing of drugs that was conducted in 2001. The methods used in this case study include observation, secondary data analysis and a comparison between the Women Hospital pharmacy figures with those of the ASHP survey which is considered to be an external benchmark as it contains a large number of hospitals that were chosen by stratified random sampling of total number of staffed beds. The results of this case study have shown that the role of pharmacists in the P&T committee needs to be extended to other vital activities. It is advisable to formalise and disseminate the results of drug use evaluation, educate prescribers about the cost of medications and to include more pharmacists attending the rounds with prescribers.